Local limit theorems for the stopping time - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. К. Алешкявичене. Локальные теоремы для времени до первого достижения в случайном блужданииA. Aleškevičienė. Lokalinės teoremos pirmo patekimo laikui atsitiktiniame klaidžiojime